DESAIN SOLAR TREE UNTUK PENERANGAN JALAN UMUM DI JALAN BYPASS NGURAH RAI BALI - Adi Darmadi, I Kadek; Dwi Giriantari, I. A.; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUM, 2023)
The road is a public facility that is quite important for the community in connecting access between regions. Public street lighting (PJU) is part of the road's complementary infrastructure which can be installed on the right or left of the road section or in the middle (on the road divider). LED is a type of lamp that is often used in PJU throughout Indonesia. In this study, solar trees are designed as a source of environmentally friendly electrical energy which will be added ongrid to the public street lighting system (PJU). This study aims to analyze the selection of the type of lamp, the capacity used and the design to be used on the Ngurah Rai Bypass Road. The location chosen from the planned Solar Tree installation is the Ngurah Rai Bypass Road for street lighting. This is intended as an application for the utilization of renewable energy, and to find out what percentage of savings is generated. The results of the tests in this study produce calculations based on the kWh meter on the Ngurah Rai Bypass Road using a solar panel of the Mono Full Screen type DHM-54X10/FS 390~420W with a maximum power of 420 watts, resulting in: First, the solar tree uses four panels with a maximum power of 1680 watts. second, the design of solar tree poles that are adequate to the conditions on the Ngurah Rai Bypass Road, namely the "Tedung" and "Kayon" shapes which will contain four panels on each pole. Third, the savings obtained from using this Solar Tree are 18.69%.